The Use of Jayanti (Sesbania Sesban) Molluscicide in Overcoming Golden Snail, Pest Of Rice Plant in The Village of Bunut Baok, Central Lombok - Suripto Suripto; Erin Ryantin Gunawan; Evy Aryanti (Universitas Mataram, 2021)
As a result of the attack golden snails, rice production declined to 30 % in some places in the province of West Nusa Tenggara. Application of science and technology activities for the community ( IbM ) to address the problem of golden snail pest have been conducted in The Village of Bunut Baok, Central Lombok. IbM program conducted by subject matter covers characteristics of jayanti plant (Sesbania sesban ) and its cultivation method, characteristics of golden snail species that is pests of the rice plant, how to prepare and manufacture of jayanti molluscicide, and its application to control rice pest snails. The methods used include lecture, discussion, demonstration and practice. IbM activity followed by 12 members of Farmers Group Mohon Petunjuk Bunut Baok Village. The results of the practice is that the use of 1 ppm solution jayanti leaf can be lethal 48% to 84% of golden snail population. Other results achieved are covering the growing appreciation of farmers to plant jayanti, increasing farmers' knowledge and skills in identifying plants jayanti, skilled to make jayanti molluscicide, and its use to control rice pest golden snails.